2010
DOI: 10.1121/1.3377080
|View full text |Cite
|
Sign up to set email alerts
|

Children’s recognition of American English consonants in noise

Abstract: In contrast to the availability of consonant confusion studies with adults, to date, no investigators have compared children's consonant confusion patterns in noise to those of adults in a single study. To examine whether children's error patterns are similar to those of adults, three groups of children ͑24 each in 4-5, 6-7, and 8-9 yrs. old͒ and 24 adult native speakers of American English ͑AE͒ performed a recognition task for 15 AE consonants in /Ä/-consonant-/Ä/ nonsense syllables presented in a background … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
48
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 31 publications
14
48
0
Order By: Relevance
“…Impaired speech sound identification may contribute to impaired phonological awareness and memory skills, thought to be strong contributing factors to the poor literacy of children with dyslexia (12)(13)(14). Second, FM system use may preferentially impact the formant transition portions of speech, which are particularly vulnerable to the degrading effects of background noise (31). Third, it is in response to this complex portion of a syllable that children with dyslexia show deficient neural encoding of timing and harmonic aspects of speech relative to their typically developing peers (9,10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired speech sound identification may contribute to impaired phonological awareness and memory skills, thought to be strong contributing factors to the poor literacy of children with dyslexia (12)(13)(14). Second, FM system use may preferentially impact the formant transition portions of speech, which are particularly vulnerable to the degrading effects of background noise (31). Third, it is in response to this complex portion of a syllable that children with dyslexia show deficient neural encoding of timing and harmonic aspects of speech relative to their typically developing peers (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Assistive listening devices (i.e., classroom FM systems) also result in neurophysiologic enhancements in response to attended vs. ignored sounds (29). Such systems increase the signalto-noise ratio of the speaker of interest (e.g., the teacher) (30) and create a more stable acoustic input by reducing the impact of background noise on the most vulnerable portion of speech sounds (31). These acoustic enhancements, along with accompanying improvements in auditory attention, lead to boosts in academic achievement, literacy, and phonological awareness, with the greatest benefits seen for children with learning impairments (32)(33)(34).…”
mentioning
confidence: 99%
“…As a signal-to-noise ratio (SNR) becomes less favorable, a listener's accuracy in perceiving the signal decreases (Stelmachowicz, Hoover, Lewis, Kortekaas, & Pittman, 2000). The ability to perceive a speech signal in adverse listening conditions, such as in the presence of noise or reverberation, increases with age until early adulthood (Crandell & Smaldino, 2000;Neuman & Hochberg, 1983;Nishi, Lewis, Hoover, Choi, & Stelmachowicz, 2010;Soli & Sullivan, 1997). Nelson and Soli (2000) suggested that acoustic environments utilizing a +15 dB SNR allow children to perceive a signal fully.…”
mentioning
confidence: 98%
“…This reduces the resources available for linguistic and cognitive processing and can often result in children 'tuning out' from being overloaded by auditory stimuli [5,38]. Noise levels are reported to be highest in the classrooms of the youngest children [25,33,47,59] which is also the age group most affected [26,32,43,45]. As children's auditory systems are neurologically immature, they have greater perceptual difficulties than adults in discriminating and understanding speech, and cannot use years of previous communicative experience to fill in missing information [58].…”
Section: Introductionmentioning
confidence: 99%